Proceedings of the 25th Pan-American Conference of Naval Engineering-COPINAVAL - Vega Sáenz, Adán.; Pereira, Newton Narciso; Carral Couce, Luis Manuel; Fraguela Formoso, José Angel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents selected contributions to the Pan-American Congress of Naval Engineering, Maritime Transport and Port Engineering (COPINAVAL), which is in its twenty-fifth edition and has become a reference event for the global maritime and port sector, attracting more and more participants from different countries. The 2017 congress was held in Panama City, Panama, bringing together a select group of scientists, entrepreneurs, academics and professionals to discuss the latest technological advances in the maritime industry.
Keywords: Offshore structures; Renewable energy sources; Transportation engineering; Traffic engineering; Offshore Engineering; Renewable Energy; Transportation Technology and Traffic Engineering